PECULIARITIES OF THYROIDAL COLLOID HORMONAL ACTIVITY OF WHITE RATS’ THYROCYTES DURING CONSUMPTION OF ORGANIC AND INORGANIC IODINE IN CONDITIONS OF POTENTIATED ALIMENTARY IODINE DEFICIENCY - Ryabukha, O.I. (World of Medicine and Biology, 2020)
Hypothyroidism occupies the major place among all disorders of the thyroid gland. The reason for this is both extensive iodine deficiency areas and the influence of natural and artificial goitrogens. The purpose of the study was to compare the effect of organic and inorganic iodine on the hormonal activity of the thyroid glands in white nonlinear male rats, which were under the conditions of alimentary iodine deficiency, potentiated by mercazolilum. Because the intensity of thyroidal colloid amino acids iodination is equivalent to the activity of hormone production, the thyroid gland activity was determined histochemically by the method of A. DesMarais & Q.N. LaHam. It was determined that organic iodine activates the thyroid gland’s hormonal activity more than inorganic iodine, while taking organic iodine the histochemical picture of the thyroid gland depended on the dose of iodine consumed and tended to normalize with its increase.